Smart Desktop Cloud Network - Jie Liu; Zhe Wang (Dianxin kexue)
As a combination application of IaaS and SaaS, virtual desktop is more and more widely used. Virtual desktop users enjoy not only remote access whenever and wherever possible, centralized controlling, but also simplified application installations and upgrades. However, there was some disadvantage concerning customer perception, especially in real-time applications. The desktop cloud data center and the access network, as well as the characteristics of desktop traffic and desktop protocol, were analyzed, an intelligent strategy control mechanism was introduced, where the strategy control center performed to enhance the service quality of access network, whilst the SDN/service chain controller optimized the processing flow in the data center. The solution aimed to enhance the virtual desktop user experience, while promoting the development of virtual desktop applications.